2023
DOI: 10.3389/fonc.2022.1033704
|View full text |Cite
|
Sign up to set email alerts
|

Canine oral squamous cell carcinoma as a spontaneous, translational model for radiation and immunology research

Abstract: IntroductionImproving outcomes for oral squamous cell carcinoma (OSCC) patients has been hindered by a lack of effective predictive animal models. Spontaneously occurring canine OSCC could help fill this gap. The objective of this study was to characterize the immune landscape of canine OSCC to advance understanding of how dogs could serve as a surrogate for human OSCC.Methods/ResultsCanine OSCC contains a heterogenous tumor immune microenvironment. CD3+ T cells were the predominant tumor infiltrating immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Our study found a higher occurrence of OSCC in mixed breed dogs, although it was also present in various pure breeds, including Poodles, Labrador Retrievers, Beagles, Boxers, Border Collies, Siberian Huskies, Pekingese, Pinschers, and Yorkshire Terriers. Despite the limited sample size, the prevalence of oral cancers in mixed breeds has also been reported in other studies of dogs [14,40]. Contrary to what is generally reported in the literature [3], our study noted that OSCC affected purebred dogs of all sizes, from minor to medium and large.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our study found a higher occurrence of OSCC in mixed breed dogs, although it was also present in various pure breeds, including Poodles, Labrador Retrievers, Beagles, Boxers, Border Collies, Siberian Huskies, Pekingese, Pinschers, and Yorkshire Terriers. Despite the limited sample size, the prevalence of oral cancers in mixed breeds has also been reported in other studies of dogs [14,40]. Contrary to what is generally reported in the literature [3], our study noted that OSCC affected purebred dogs of all sizes, from minor to medium and large.…”
Section: Discussionsupporting
confidence: 52%
“…In dogs, there is no concrete evidence linking oral SCC in dogs with tobacco smoke exposure. Consequently, dogs are being considered as a comparative model for researching OSCCs not linked to alcohol and tobacco, which are about 10-15% of the total OSCC cases in humans [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the median age of dogs diagnosed with oral SCC was about 11 years, with a higher occurrence in males than females. The general treatment protocol for patients with oral SCC involves either chemoradiation or aggressive surgical removal of the tumor, followed by radiation therapy (RT) with or without chemotherapy [ 24 ]. Interestingly, a recent study has indicated that combining RT with immunotherapy may lead to improved response rates in dogs, similar to findings observed in humans [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSU has also recently studied the immune landscape of canine oral squamous cell carcinoma to combine radiation therapy and immunotherapy in canines. Future studies may contribute to developing novel therapies in human patients [ 51 ].…”
Section: Future Research Contributions From Companion Animals and Vet...mentioning
confidence: 99%